2015
DOI: 10.1002/ejlt.201400663
|View full text |Cite
|
Sign up to set email alerts
|

Fortification of chocolate milk with omega‐3, omega‐6, and vitamins E and C by using liposomes

Abstract: The main goal of this work was to develop an additive to fortify a widely consumed product with vitamins. Additives were made of soy phosphatidylcholine (SPC)‐based liposomes to encapsulate vitamin E (VE) and vitamin C (VC), and incorporated in chocolate milk to generate a functional food and posterior pasteurization. SPC contains essential fatty acids like omega‐3 and omega‐6 fatty acids. Stearic acid (SA) or calcium stearate (CaS) was incorporated as a liposome bilayer stabilizer. Characterization of liposom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Furthermore, liposomes are nontoxic, biocompatible and biodegradable and can be produced by inexpensive, safe and natural sources of phospholipids (e.g., soybean, egg yolk) in large‐scale for food and pharmaceutical applications. Liposomes also enhance stability and solubility of entrapped compounds in food systems and gastrointestinal tract; consequently, increase their functionality and bioavailability …”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore, liposomes are nontoxic, biocompatible and biodegradable and can be produced by inexpensive, safe and natural sources of phospholipids (e.g., soybean, egg yolk) in large‐scale for food and pharmaceutical applications. Liposomes also enhance stability and solubility of entrapped compounds in food systems and gastrointestinal tract; consequently, increase their functionality and bioavailability …”
Section: Introductionsupporting
confidence: 72%
“…However, some problems have greatly restricted applications of phenolic compounds in food systems. The main limitations for direct use of phenolic compounds are related to their conditioned solubility, low stability, unfavorable taste, low bioavailability, and reaction with food ingredients such as proteins . Encapsulation of phenolic compounds in liposomal systems provides a promising and suitable way to overcome these drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Results from our laboratory have shown that formulations of SPC with stearic acid or innovative addition of calcium stearate, in the same molar ratio, resulted in an improvement regarding oxidative stability and protection of thermolabile vitamins [32]. On the other hand, these formulations did not induce any unpleasant flavor when added to milk or orange juice, so they can be applied in food commercial products [32][33][34][35].…”
Section: Improvement Of Soybean Lecithin By Addition Of Calcium Stearmentioning
confidence: 96%
“…In particular, vitamin C encapsulated in liposomes retains 50% of its activity after 50 days in refrigerated storage, whereas non-encapsulated vitamin loses its activity after 19 days. Also, liposomes present an important protective effect over thermolabile vitamin C, shown by an antioxidant action after pasteurization [32,34,35,49].…”
Section: Processing Issues In Adding Vitamins E and C Protected With mentioning
confidence: 99%
See 1 more Smart Citation